Circular - Garrett, G. T.
1938-02 038-0170-002 number of children who, for various reasons, either because their parents are themselves refugees or because they have no homes at all to go to, must be kept here indefinitely unless the Committee's hands are forced for economic reasons. A child ''adopted" is therefore a child saved. A penny a week from employees in a large Works would go a long way towards ''adopting" and saving some of these children. The propaganda campaign against the children has so far succeeded that large sections of the public think that they have all gone home, or that they should go home and have homes to go to, and in some quarters, support for them is temporarily drying up. This must be overcome if our duty to the children is to be carried out. Everything depends on the greatest possible personal, sacrifice and energy from all those connected with the Committees. Yours sincerely, G.T. GARRATT Hon. Administrator. 292/946/38/170(II)